A Rare Condition in Child Psychiatry Practice: Childhood Disintegrative Disorder - Yazici, Kemal Utku; Percinel, Ipek (Yerkure Tanitim & Yayincilik Hizmetleri A S, 2014)
Childhood disintegrative disorder is a very rare pervasive developmental disorder characterized by normal development of verbal and nonverbal communication skills, social interaction, play, bladder and bowel control and motor behavior at least in the first two years, followed by regression between 2-10 years of age in two or more of the mentioned developmental areas. Estimated prevalence of the childhood disintegrative disorder is around 1.1-6.4 per 100.000 children and the common age of onset is 3.36 years. The present report describes a boy who developed childhood disintegrative disorder after approximately 3 years of normal development and clinical features are discussed in the light of the clinical literature.
Keywords: Childhood; disintegrative disorder; pervasive developmental disorder